Gender inequality in early initiation of breastfeeding in Bangladesh: a trend analysis - Kanchan Kumar Sen; Taslim Sazzad Mallick; Wasimul Bari (BMC, 2020)
Abstract Background Early initiation of breastfeeding within 1 hour after birth is essential for newborns, because it reduces risk of neonatal mortality and hypothermia to a great extent and also helps in preventing the long-term chronic diseases and in increasing energy and immunity to newborn. In order to reach the 'very good state' of timely or early initiation of breastfeeding recommended by WHO, Bangladesh needs to increase the current rate of 51.24 to 100%. An attempt has been made in this study to examine how the early breastfeeding practice changes among male and female children with time controlling the factors associated with this practice. Methods Data from last four consecutive Bangladesh Demographic and Health Surveys (BDHS) have been used in the study. The participants were included whose child born within the last 5 years preceding the surveys of 2004, 2007 and 2011, and within the last 3 years preceding the survey of 2014 in the study and the respective selected participants were 5145, 4765, 7099 and 4370. To conduct the trend analysis, the descriptive statistics of selected variables along with prevalence of early initiation of breastfeeding have been computed by different years and a multiple logistic regression model has been fitted to the pooled dataset of 2004-2014 considering survey years as time. Results Rate of early initiation of breastfeeding increased as time progressed and it was faster for female child compared to male child. For example, female children were significantly 10 and 6% less likely to be initiated early than their counterparts in 2004 and 2007, respectively; whereas after 2007 both male and female children were equally treated for breastfeeding practice. It was also found that rate of early initiation significantly increased for one unit increased in survey year and this increasing rate was higher for female child compared to male child. For example, for one unit of increased in survey year, the early initiation of breastfeeding increased by 60% for male child and by 67% for female child. Besides, survey time, gender, education of parents, wanted index child, mode of delivery, antenatal care visits, wealth index, exposure to media and division were found to have potential influence on early initiation of breastfeeding. Conclusion Demographic and health surveys conducted in Bangladesh since 2011 have shown no evidence of gender discrimination regarding timely initiation of breastfeeding. In order to achieve the target rate of early initiation of breastfeeding recommended by WHO, it requires to take effective intervention regarding maternal and child health education.